Eagle syndrome as a rare cause of recurrent transient ischemic stroke in Senegal (West Africa) - Loum, Birame; Lame, Cheikh Ahmedou; Ndiaye, Cheikhna B.; Toure, Kamadore; Ndiaye, Mouhamadou Mansour (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Eagle syndrome is a rare condition, often characterized by nonspecific symptoms. It is due to an abnormally long or compressive styloid process on surrounding structures. Exceptionally, it can cause neuro-vascular manifestations. We report an observation of Eagle syndrome discovered incidentally in presence of recurrent transient ischemic stroke. A 74-year-old man with no cardiovascular risk factors, was admitted to our department following 4 episodes of transient ischemic stroke with right hemiplegia and aphasia, always rapidly resolving. Head and neck CT scan showed 2 long styloid processes with a marked impingement of the left one against the ipsilateral internal carotid artery. Intraoral styloidectomy was performed. The patient recovered fully and remained free of symptoms without neurological impairment, at 6 months. Eagle syndrome is a rare condition which may lead, exceptionally, to repetitive transient ischemic stroke. Surgical styloidectomy must be considered to reduce the risk of new vascular events and prevent serious complications such as dissection of the internal carotid artery.